2013
DOI: 10.1073/pnas.1214551110
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network connectivity distinguishes chemotherapy-treated breast cancer survivors from controls

Abstract: Breast cancer (BC) chemotherapy is associated with cognitive changes including persistent deficits in some individuals. We tested the accuracy of default mode network (DMN) resting state functional connectivity patterns in discriminating chemotherapy treated (C+) from non–chemotherapy (C−) treated BC survivors and healthy controls (HC). We also examined the relationship between DMN connectivity patterns and cognitive function. Multivariate pattern analysis was used to classify 30 C+, 27 C−, and 24 HC, which sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
98
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 44 publications
3
98
3
2
Order By: Relevance
“…Functional connectivity preprocessing was performed using Statistical Parametric Mapping 8 (SPM8, RRID:SCR_007037) and CONN Toolbox (RRID:SCR_009550) as previously described (Kesler & Blayney, 2015; Kesler et al., 2013, 2014). Successful normalization was confirmed via visual inspection using the check registration function in SPM8 and in‐house software that creates whole volume slice montages.…”
Section: Methodsmentioning
confidence: 99%
“…Functional connectivity preprocessing was performed using Statistical Parametric Mapping 8 (SPM8, RRID:SCR_007037) and CONN Toolbox (RRID:SCR_009550) as previously described (Kesler & Blayney, 2015; Kesler et al., 2013, 2014). Successful normalization was confirmed via visual inspection using the check registration function in SPM8 and in‐house software that creates whole volume slice montages.…”
Section: Methodsmentioning
confidence: 99%
“…Research in this domain has traditionally focused on the chronic psychosocial late effects, such as impairments in quality of life, persistent fatigue, depression, and anxiety (Day et al 1999; Ganz et al 1995, 1998; Goodwin et al 2003; Land et al 2006). More recent research endeavors have broadened to include investigation of long-term cognitive impairments in early breast cancer patients (Ahles et al 2002; Jim et al 2012; Phillips et al 2012; Kesler et al 2013). This work has demonstrated that standard breast cancer adjuvant therapy, particularly treatment with chemotherapy, is associated with adverse cognitive functioning, including impairments in memory, processing speed, and executive function (Ahles et al 2002; Jim et al 2012; Phillips et al 2012), which may persist up to 20 years following the completion of primary adjuvant therapy (Koppelmans et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…15 These cognitive impairments can be long-lasting and tend to be one of the most common limitations to quality of life and well-being. 6,7 There is growing concern that chemotherapy may increase the risk for later neurodegenerative conditions by altering or accelerating brain-aging processes.…”
mentioning
confidence: 99%